PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KARAKTER WIRAUSAHA TERHADAP PENINGKATAN PERILAKU INTRAPRENEURSHIP DALAM PERGURUAN TINGGI SWASTA - Novie Noordiana Rachma Yulia; Fauzi Arif Rohman Hakim; Agung Pribadhi (STIE Mahardhika, 2023)
All organizations as well as the Higher Education Industry need to be prepared and improve in order to keep up with fluctuated environment. Because the revenue generating for universities doesn’t always come from tuition fee, having Business Center is a solution to overcome financing problems and rise revenue as well as prosperity for organizational members within the universities. To achieve it, the members of the organization need to have an entrepreneurial spirit and intrapreneurship conduct. It is concluded that the growth and development of intrapreneurship behavior among lecturers and staff within the university is influenced by the transformational leadership style of the chancellor. This research purpose is to analyze factors to increase intrapreneurship behavior (Behavioral Intrapreneurship) among organizational members in one of the PTS located in West Surabaya. The examination method used in this study is a qualitative technique with a case study method at a PTS in West Surabaya and uses a quantitative technique using the percentage method for descriptive analysis of each variable. From the outcome concluded that the chancellors at the universities studied have a transformational leadership style while the lecturers and employees at the universities have entrepreneurial character and entrepreneurial behavior. The conclusion of this study is that the formation of intrapreneurship behavior in the college environment influenced by the transformational leadership style of the leader and entrepreneurial character of the member of the college environment.